Modeling the spatial and temporal correlations between solar, wind and hydro power generation in Spain - Lee, Jeonghyeon (My University, 2025)
El objetivo de este proyecto es analizar la información pública disponible en ESIOS relacionada con la generación de energía renovable. Se estudiarán las series de producción eólica, solar e hidroeléctrica. Las características de cada variable se analizarán de forma individual y conjunta, teniendo en cuenta las dimensiones temporal y espacial. Para ello, se ha automatizado la recopilación de toda la información necesaria para el estudio en un almacén interno específicamente diseñado para facilitar el análisis.

The purpose of this project is to analyze the public information available in ESIOS related to renewable power generation. We will study the series of wind, solar and hydroelectric production using machine learning techniques. The characteristics of each variable will be analyzed individually and jointly, taking in consideration of the temporal and spatial dimensions. To this end, we automate the collection of all the information needed for the study in an internal warehouse specifically designed to facilitate analysis.
Máster Universitario en Big Data
Keywords: H0Z